(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Drowning in India commonly occurs in rivers, ponds, lakes and wells and can be accidental, suicidal or sometimes homicidal. In cities like Bangalore deaths due to drowning takes place in tanks, water sumps, wells and swimming pools. A five retrospective study of deaths due to drowning in water sumps was undertaken in the department of Forensic medicine, MS Ramaiah Medical College, Bangalore. A total of 112 (100%) deaths were due to drowning of which 34 (30%) cases of drowning was in water sumps. The study revealed that females 19 (55.90%) outnumbered the males and children in the age group of 0-10 (55.88%) accounted for the ma jority of the cases, (73.3%) were mainly accidental in manners, (44.10%) had taken place be tween 12 noon to 6 pm. This new source of water body has been a watery grave which is very unfortunate and Supervision turns out to be the key contributor to these unfortunate preventable deaths.